Coping strategies for household water insecurity in rural Gambia, mediating factors in the relationship between weather, water and health - Indira Bose; Robert Dreibelbis; Rosemary Green; Kris A. Murray; Omar Ceesay; Sari Kovats (BMC, 2024)
Abstract Background Rural communities in low- and middle-income countries, such as The Gambia, often experience water insecurity periodically due to climate drivers such as heavy rainfall and reduced rainfall, as well as non-climate drivers such as infrastructural issues and seasonal workloads. When facing these challenges households use a variety of coping mechanisms that could pose a risk to health. We aimed to understand the drivers of water insecurity (climate and non-climate), the behavioural responses to water insecurity and the risks these responses pose to the health of communities in rural Gambia and map these findings onto a conceptual framework. Methods We interviewed 46 participants using multiple qualitative methods. This included in-depth interviews and transect walks. A subset of 27 participants took part in three participatory pile-sorting activities. In these activities participants were asked to rank water-related activities, intrahousehold prioritisation of water, and the coping strategies utilised when facing water insecurity. Results Multiple strategies were identified that people used to cope with water shortages, including: reductions in hygiene, changes to food consumption, and storing water for long periods. Many of these could inadvertently introduce risks for health. For example, limiting handwashing increases the risk of water-washed diseases. Deprioritising cooking foods such as millet, which is a nutrient-dense staple food, due to the high water requirements during preparation, could impact nutritional status. Additionally, storing water for long periods could erode water quality. Social factors appeared to play an important role in the prioritisation of domestic water-use when faced with water shortages. For example, face-washing was often maintained for social reasons. Health and religion were also key influencing factors. People often tried to protect children from the effects of water insecurity, particularly school-aged children, but given the communal nature of many activities this was not always possible. Many people associated water insecurity with poor health. Conclusions To reduce the risks to health, interventions need to address the drivers of water insecurity to reduce the need for these risky coping behaviours. In the short term, the promotion of behavioural adaptations that can help buffer health risks, such as water treatment, may be beneficial.